Descriptive Analysis of Environmental and Community Practices in the Indonesian Mining Sector: Contributions to Sustainable Development Goals - Sumartanto, Mukhlas; Arviansyah , Arviansyah (Riviera Publishing, 2025)
Sustainable development in the mining sector demands comprehensive practices that ensure environmental preservation and empower local communities. This study aims to descriptively analyze the implementation of Environmental Sustainability Practice (ESP) and Community Development Practice (CDP) in Indonesian mining companies, highlighting their contribution to achieving the Sustainable Development Goals (SDGs). Utilizing a descriptive-analytical approach, primary data were collected through surveys distributed to operational managers across various mining sites. Statistical indicators such as mean, standard deviation, variance, skewness, and kurtosis were employed to examine patterns and variability. The findings reveal that ESP initiatives are moderately implemented, reflecting a consistent effort toward environmental management and resource conservation, whereas CDP shows uneven performance, particularly in stakeholder engagement and socio-economic development programs. Discussions underscore geographical disparities and commodity-specific influences that affect the effectiveness of these practices. It is concluded that, although mining companies have made notable progress towards sustainable practices, significant gaps remain in optimizing community development outcomes. Strengthening regulatory frameworks and encouraging best-practice adoption are crucial to closing these gaps. This study provides empirical insights for policymakers, industry practitioners, and researchers striving to advance sustainable mining operations in emerging economies.